Determination of heat-transfer coefficient in casting-die system - Kovač, Risto (Journal of Production Engineering, 1984)
The intensity of casting-cooling is determined by the heat-transfer coefficient between the casting and the die, and it represents important parameter of the system. In this paper, the method determination of this coefficient and its approximate value is shown. This method is used in analytic analysis process of casting solidification and in practice also for marking the cooling intensity and its influence on the structure and the mechanical properties of castings.